2011
DOI: 10.1007/s10067-010-1658-1
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu’s arteritis progression on anti-TNF biologics: a case series

Abstract: Takayasu's arteritis (TA) is a rare granulomatous vasculitic disease that affects the aorta and its major branches. Recent studies have suggested that anti-TNFα biological therapies are highly effective in treating TA refractory to conventional immunosuppressive therapy. We describe two patients with TA: one with progressive TA despite management with two different anti-TNFα agents, infliximab and adalimumab, and another who developed TA while treated with infliximab for the management of pre-existing Crohn's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…6 Preliminary studies have reported the efficacy of biological-targeting treatments such as TNF-α antagonists (infliximab, adalimumab, etanercept) and anti-IL-6 receptor (tocilizumab) in TA refractory to other immunosuppressive therapies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we report the long-term outcome of 49 TA patients treated with TNF-α antagonists and tocilizumab in this French nationwide study, and we compare their safety, their efficacy, and the factors predictive of treatment response.…”
Section: Editorial See P 1685 Clinical Perspective On P 1700mentioning
confidence: 99%
“…6 Preliminary studies have reported the efficacy of biological-targeting treatments such as TNF-α antagonists (infliximab, adalimumab, etanercept) and anti-IL-6 receptor (tocilizumab) in TA refractory to other immunosuppressive therapies. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Here, we report the long-term outcome of 49 TA patients treated with TNF-α antagonists and tocilizumab in this French nationwide study, and we compare their safety, their efficacy, and the factors predictive of treatment response.…”
Section: Editorial See P 1685 Clinical Perspective On P 1700mentioning
confidence: 99%
“…Los corticoides han demostrado disminuir hasta en 50% la progresión de las lesiones y la terapia inmunosupresora evita la re-estenosis (14) . Al ser irreversible la estenosis, la angioplastia precoz es necesaria para el manejo de la hipertensión renovascular y prevención de complicaciones (15) .…”
Section: Discussionunclassified
“…The clinical prognosis of the disease is variable; use of corticosteroid decreases progression of the lesion by 50%. Immunosupressive treatment provides better disease control and prevents recurrence of stenosis (13). Angioplasty is efficient in treatment of TA and increases 5-year survivial up to 80-95%.…”
Section: Takayasu Arteritismentioning
confidence: 99%